Impact of Packaging Materials and Storage Duration on the Physical Properties of Mantangan (Merremia peltata)-Based Complete Wafers - Fakhri, Saitul; Purba, Cici Franika; Harianja, Ester; Akmal; Suparjo; Kaswari, Teja; Novianti, Sri; Suryani, Heni (Faculty of Animal Science, Universitas Brawijaya, 2024)
This study evaluated how packaging materials (PM) and storage duration (SD) influence the physical properties of mantangan-based complete wafers (MbCW). The MbCW formulation consisted of 44% Merremia peltata, 16% Brachiaria mutica, and 40% concentrate. Ingredients were ground (2 mm), homogenized, steamed, and pressed to produce wafers. A 4 × 3 factorial completely randomized design assessed four PM types (WP: no packaging, PL: plastic, CB: cardboard, PS: plastic sack) and three SD levels (30, 60, and 90 days). Statistical analyses revealed significant PM × SD interactions (p < 0.01) for moisture content, impact resistance, and water absorption. SD alone affected density, specific gravity, shrinkage, and fungal concentration. Moisture content and water absorption increased over time, while plastic packaging uniquely improved impact resistance with extended storage. Other packaging types showed decreased impact resistance. Plastic packaging demonstrated superior performance, preventing fungal growth for up to 90 days, with only 1.06% mould at this time, compared to 4.43% without packaging. The effective shelf lives were 57, 54, 53, and 43 days for PL, CB, PS, and WP, respectively. In conclusion, plastic was the optimal packaging material for MbCW storage.